Galactic synchrotron emissivity measurements between 250° < l < 355° from the GLEAM survey with the MWA - Su, H.; Hurley-Walker, Natasha; Jackson, Carole; McClure-Griffiths, N.; Tingay, Steven; Hindson, L.; Hancock, P.; Wayth, Randall; Gaensler, B.; Staveley-Smith, L.; Morgan, J.; Johnston-Hollitt, M.; et al. (Oxford University Press, 2017)
Synchrotron emission pervades the Galactic plane at low radio frequencies, originating from cosmic ray electrons interacting with the Galactic magnetic field. Using a low-frequency radio telescope, the Murchison Widefield Array (MWA), we measure the free-free absorption of this Galactic synchrotron emission by intervening HII regions along the line of sight. These absorption measurements allow us to calculate the Galactic cosmic ray electron emissivity behind and in front of 47 detected HII regions in the region 250° < l < 355°, |b| < 2°.We find that all average emissivities between the HII regions and the Galactic edge along the line of sight (eb) are in the range of 0.39 ~ 1.45 K pc-1 with a mean of 0.77 K pc-1 and a variance of 0.14 K pc-1 at 88 MHz. Our best model, the two-circle model, divides the Galactic disc into three regions using two circles centring on the Galactic Centre. It shows a high emissivity region near the Galactic Centre, a low emissivity region near the Galactic edge, and a medium emissivity region between these two regions, contrary to the trend found by previous studies.